Health Risk Assessment of Human Exposure to Dust Exposure on Communities Around Weaving Industry in Palembang, Indonesia - Maksuk Maksuk; Intan Kumalasari; Sherli Shobur (International Journal of Advanced Health Science and Technology, 2022)
Air pollution due to industrial activities is increasing worldwide, including in Indonesia. Particulate Matter (PM) is one of the air pollutant parameters that can cause health problems, especially respiratory problems in communities living at the weaving industrial area. The aimed of this study was to analyze the environmental health risk  of human exposure due to dust exposure in communities around the weaving industry center. This research was an observational study using an environmental health risk analysis approach. Dust parameters were measured in as many as ten indoors and five outdoors around the weaving industry. The dust parameters measured were PM 2.5, PM 10, and Total Solid Particulate (TSP) concentration indoor and outdoor around the weaving industry areas. Dust measurements were carried out in the morning and afternoon using an Aerocet. The average results of dust measurement indoor were PM 2.5 (0.182 mg/m3), PM 10 (0.443 mg/m3), TSP (0.556 mg/m3), while for outdoor PM 2.5 (0.185 mg/m3). PM 10 (0.381 mg/m3), TSP (0.419 mg/m3). The average indoor of PM 2.5 intake was 0.013 mg/kg-day, PM10 (0.031 mg/kg-day), and TSP (0.038 mg/kg-day), and outdoor were PM 2.5 (for adult 0.064 mg/kg-day, for children 0.014 mg/kg-day), PM10 (for adult 0.132 mg/kg-day and for children 0.292 mg/kg-day), TSP (for adult 0.146 mg/kg-day and for children 0.322 mg/kg-day). All of them were more than Reference Concentration (RfC), and the Risk Quotient of PM10 and PM2.5 were more than 1. Exposure to PM10 and PM2.5 are unsafe or likely to result in non-carcinogenic effects on the residents in the next 30 years. The finding of this study is to provide information the dust concentration in the environment, the Risk Quotient of dust exposure in the communities around the weaving industry, and strategies for managing risks due to dust exposure in the traditional weaving industry center. Therefore, it is necessary to conduct a risk management scenario.